Sex-specific overdominance at the maturation vgll3 gene for reproductive fitness in wild Atlantic salmon - Mobley, Kenyon B.; Barton, Henry J.; Ellmén, Mikko; Ruokolainen, Annukka; Guttorm, Olavi; Pieski, Hans; Orell, Panu; Erkinaro, Jaakko; Primmer, Craig R. (Wiley-Blackwell, 2024)
Linking reproductive fitness with adaptive traits at the genomic level can shed light on the mechanisms that produce and maintain sex-specific selection. Here, we construct a multigenerational pedigree to investigate sex-specific selection on a maturation gene, vgll3, in a wild Atlantic salmon population. The vgll3 locus is responsible for ~40% of the variation in maturation (sea age at first reproduction). Genetic parentage analysis was conducted on 18,265 juveniles (parr) and 685 adults collected at the same spawning ground over eight consecutive years. A high proportion of females (26%) were iteroparous and reproduced two to four times in their lifetime. A smaller proportion of males (9%) spawned at least twice in their lifetime. Sex-specific patterns of reproductive fitness were related to vgll3 genotype. Females showed a pattern of overdominance where vgll3*EL genotypes had three-fold more total offspring than homozygous females. In contrast, males demonstrated that late-maturing vgll3*LL individuals had two-fold more offspring than either vgll3*EE or vgll3*EL males. Taken together, these data suggest that balancing selection in females contributes to the maintenance of variation at this locus via increased fitness of iteroparous vgll3*EL females. This study demonstrates the utility of multigenerational pedigrees for uncovering complex patterns of reproduction, sex-specific selection and the maintenance of genetic variation.
Keywords: life-history; mating success; reproductive success; sexual conflict; sexual selection; trade-off